Demystifying the estimation of reactivity ratios for terpolymerization systems. Issue 5 (18th March 2014) - Kazemi, Niousha; Duever, Thomas A.; Penlidis, Alexander
<x xml:space="preserve">Abstract</x> In typical practice for terpolymerizations so far, binary reactivity ratios have been used directly in the instantaneous Alfrey and Goldfinger (AG) model, effectively ignoring the presence of the third monomer. In addition, the use of the AG model leads to severe estimation problems, if one would like to estimate reactivity ratios from experimental data. Due to the above reasons, the AG model was recast and was subsequently used with terpolymerization data directly to estimate ternary reactivity ratios under the error‐in‐variables‐model framework, based both on instantaneous (low conversion) and cumulative composition data (medium and high conversions). Several examples and counter examples highlight such important issues as the choice of the correct number of responses, accounting for the appropriate error structure, and incorporating the right information content, all with diagnostic checks whose target is the eventual reliability of the reactivity ratio estimates. © 2014 American Institute of Chemical Engineers AIChE J, 60: 1752–1766, 2014